The exhibitionist eaudiobook - Mendelson, Charlotte (Macmillan Audio, 2023)
This program is narrated by multi-award-winning actor Juliet Stevenson. THE TIMES (UK) NOVEL OF THE YEAR Named A BEST BOOK OF THE YEAR by the Guardian, the Telegraph, and the Sunday Times (UK) Charlotte Mendelson's The Exhibitionist is a "furiously funny" novel ( Sunday Express , UK) about a marriage between two artists, Lucia and Ray, which begins to unravel over the course of one weekend. Meet the Hanrahan family, gathering for a momentous weekend as famous artist and notorious egoist Ray Hanrahan prepares for a new exhibition of his art–the first in many decades–and one he is sure will burnish his reputation for good. His three children will be there: eldest daughter Leah, always her father's biggest champion; son Patrick, who has finally decided to strike out on his own; and daughter Jess, the youngest, who has her own momentous decision to make. And what of Lucia, Ray's steadfast and selfless wife? She is an artist, too, but has always had to put her roles as wife and mother first. What will happen if she decides to change? For Lucia is hiding secrets of her own, and as the weekend unfolds and the exhibition approaches, she must finally make a choice about which desires to follow. The Exhibitionist is the latest, extraordinary novel from Charlotte Mendelson, a dazzling exploration of art, sacrifice, toxic family politics, queer desire, and personal freedom. A Macmillan Audio production from St. Martin's Press.